Significance of Skills in Transformational Leadership in the National Department for Culture and Arts in Kuching, Sarawak - Shazia Shaheena, Shah (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is focusing on to identify the types and significance ofskills in transformational leadership in The National Department for Culture and Arts (JKKN) federal department in Kuching, Sarawak:. This study has used qualitative method in order to collect data to conduct this research in detailed. Bass and burn transfonnationalleadership theory has been used to support my research result. It is expecting to bridge the gap and identify which type of leadership skills in transfonnationalleadership is used in JKKN federal department in Kuching, Sarawak.